INDONESIA’S CHAIRMANSHIP OF IORA 2015-2017 AND BEYOND - Sigit Aris Prasetyo (Jurnal Kajian Wilayah, 2016)
Development of Indian Ocean Rim Association (IORA) as is still an underdevelopeda regional cooperation forum is still slow and underdeveloped, even though it has potential to become a strong international organization. This paper aims to analyze how and what are Indonesia’s role, as the chairman of IORA in 2015-2017, in addressing the challenges and opportunities for the next two years. These challenges are, for instance, the low level of enthusiasm of member countries, and how IORA create tangible or concrete results to its state members. This paper also provides several recommendations for Indonesia to revitalize its policy orientation, which should give greater attention to the Indian Ocean and IORA in line with the doctrine of maritime fulcrum. Keywords: IORA, Indian Ocean, challenges, opportunities, chairmanship, maritime fulcrum.Abstrak Perkembangan Indian Ocean Rim Association (IORA) sebagai forum kerja sama regional masih tergolong lambat dan belum maju, walaupun sebenarnya memiliki modalitas yang kuat, bahkan dapat menjadi salah satu forum kerja sama internasional yang kuat. Tulisan ini bertujuan untuk melihat bagaimana dan peran apa yang bisa dimainkan Indonesia sebagai ketua IORA selama periode tahun 2015-2017 dalam menjawab tantangan dan peluang dalam dua tahun ke depan. Tantangan-tantangan seperti masih minimnya antusiasme negara-negara anggota, dan belum fokusnya bidang kerja sama yang selama ini telah dilakukan perlu segera diselesaikan. Tulisan ini juga memberikan beberapa saran atau rekomendasi usulan bagaimana Indonesia sebagai ketua IORA dapat merevitalisasi orientasi kebijakannya, yang salah satunya yaitu dengan memberikan perhatian yang lebih kepada Samudera Hindia dan IORA sejalan dengan doktrin Poros Maritim. Kata kunci: IORA, Samudera Hindia, tantangan, peluang, keketuaan, poros maritim.